2022
DOI: 10.1002/bdr2.2112
|View full text |Cite
|
Sign up to set email alerts
|

Validation of case definition algorithms for the ascertainment of congenital anomalies

Abstract: Background Congenital anomalies (CA) are one of the leading causes of infant mortality and long‐term disability. Many jurisdictions rely on health administrative data to monitor these conditions. Case definition algorithms can be used to monitor CA; however, validation of these algorithms is needed to understand the strengths and limitations of the data. This study aimed to validate case definition algorithms used in a CA surveillance system in British Columbia (BC), Canada. Methods A cohort of births between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Measures of sensitivity were lower than PPVs for posterior urethral valve and/or prune belly, renal dysgenesis, and hypospadias. A study conducted among a cohort of births in British Columbia reported comparable results, with urinary tract defects having the lowest PPV (83.3%) and sensitivity (67.3%) of all group defects (Nava de Escalante et al, 2022). Researchers noted sensitivity was lower for this system due to a greater likelihood of missed diagnosis at birth and a longer ascertainment period.…”
Section: Discussionmentioning
confidence: 89%
“…Measures of sensitivity were lower than PPVs for posterior urethral valve and/or prune belly, renal dysgenesis, and hypospadias. A study conducted among a cohort of births in British Columbia reported comparable results, with urinary tract defects having the lowest PPV (83.3%) and sensitivity (67.3%) of all group defects (Nava de Escalante et al, 2022). Researchers noted sensitivity was lower for this system due to a greater likelihood of missed diagnosis at birth and a longer ascertainment period.…”
Section: Discussionmentioning
confidence: 89%